(untitled) (Journal of actual problems of jurisprudence, 2018)
The article gives the genesis, formation and development stages of the Institute of state service in the Republic of Kazakhstan, as well as the concept of public service in various aspects. The importance and role of public service as a public-legal institution, providing socio-economic and political changes in the country, constantly increases in connection with the formation of a new state in Kazakhstan. Public service is the actual strategic part of achieving public policy objectives. The formation of an effective system of state power in the republic, corresponding to the standards of the rule of law, is continuously associated with the development of the institution of public service. The article analyzes the formation and peculiarities of the civil service institution in some states of the Anglo-Saxon and Romano-German legal systems. Also discusses the regulatory framework of the Republic of Kazakhstan in the sphere of public service, which is an important tool for defining activities, establishing the legal status of civil servants and other key components of this legal Institute. Feature of the work is that the authors give a detailed analysis of the stages of formation and development of public service, as a professional activity to ensure the implementation of public functions, a key element of the functional component of the mechanism of public administration. In conclusion, the authors note the importance of public service as a political institution aimed at improving public administration, in order to strengthen the sovereign state and the development of civil society. Key words: public service, development stages, the mechanism of public administration, the practice of foreign countries, the legal institution.